Synthesis and Validation of a Hydroxypyrone-Based, Potent, and Specific Matrix Metalloproteinase-12 Inhibitor with Anti-Inflammatory Activity In Vitro and In Vivo - J. Aerts; R. E. Vandenbroucke; R. Dera; S. Balusu; E. Van Wonterghem; L. Moons; C. Libert; W. Dehaen; L. Arckens (Hindawi Limited, 2015)
A hydroxypyrone-based matrix metalloproteinase (MMP) inhibitor was synthesized and assayed for its inhibitory capacity towards a panel of ten different MMPs. The compound exhibited selective inhibition towards MMP-12. The effects of inhibition of MMP-12 on endotoxemia and inflammation-induced blood-cerebrospinal fluid barrier (BCSFB) disruption were assessed both in vitro and in vivo. Similar to MMP-12 deficient mice, inhibitor-treated mice displayed significantly lower lipopolysaccharide- (LPS-) induced lethality compared to vehicle treated controls. Following LPS injection Mmp-12 mRNA expression was massively upregulated in choroid plexus tissue and a concomitant increase in BCSFB permeability was observed, which was restricted in inhibitor-treated mice. Moreover, an LPS-induced decrease in tight junction permeability of primary choroid plexus epithelial cells was attenuated by inhibitor application in vitro. Taken together, this hydroxypyrone-based inhibitor is selective towards MMP-12 and displays anti-inflammatory activity in vitro and in vivo.